Let local voices be heard: a tale of partnership for e-Government. Issue 6 (18th August 2022) - Paksi, Arie; Yoon, Seongwon; Anand, Prathivadi; Lee, Kiyoung
ABSTRACT: This article aims to uncover the ways in which different, yet closely related, discourses on the Indonesia–Korea e-Government partnerships are constructed and evaluated through the lens of donor–recipient cross narratives. The current frameworks for measuring and evaluating the effects of e-Government have given too much attention to the material dimension, thereby falling short of providing a holistic view of the discourse on the partnerships. To provide analysis that best represents the main discursive points articulated by principal actors, we developed a more comprehensive conceptual framework that encompasses both ideational and material dimensions.